A grain based modeling study of mineralogical factors affecting strength, elastic behavior and micro fracture development during compression tests in granites. (October 2015) - Hofmann, Hannes; Babadagli, Tayfun; Yoon, Jeoung Seok; Zang, Arno; Zimmermann, Günter
Highlights: GBM can reproduce strength and elastic properties of granites. Properties of multiple granites could not be matched simultaneously. Crack development strongly depends on mineral and particle distribution. Heterogeneity of rocks and rock masses is properly represented by DEM. Abstract: The influence of mineral size and distribution, and model discretization on elastic rock properties, rock strength, and types and numbers of micro cracks was studied numerically using a two-dimensional discrete element grain based modeling (GBM) approach. The model was calibrated to unconfined and confined compression tests and Brazilian tensile tests performed on Aue granite. Confined asymmetric compression tests were simulated for the same rock and compared to physical fracture paths. The GBM approach is able to reproduce all major laboratory observations including the correct ratio between compression strength and Brazilian tensile strength that cannot be captured with earlier contact models.